2020
DOI: 10.3390/ijms21165889
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Effects of Silver Nanoparticles on Monogenean Parasites: Lessons from Caenorhabditis elegans

Abstract: The mechanisms of action of silver nanoparticles (AgNPs) in monogenean parasites of the genus Cichlidogyrus were investigated through a microarray hybridization approach using genomic information from the nematode Caenorhabditis elegans. The effects of two concentrations of AgNPs were explored, low (6 µg/L Ag) and high (36 µg/L Ag). Microarray analysis revealed that both concentrations of AgNPs activated similar biological processes, although by different mechanisms. Expression profiles included genes involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 146 publications
(144 reference statements)
0
3
0
Order By: Relevance
“…not necessarily causing cuticle damage). Pimentel-Acosta et al [14] also reported that silver nanoparticles at high and low concentrations activated dysregulation of similar biological processes (detoxi cation, neurotoxicity, modulation of cell signalling, embryonic development, reproduction, and tegument organization) by different mechanisms in metazoan parasites of sh. Since cuticle can act as a diffusion barrier for various anthelmintic compounds [15], combination of silver with conventional anthelmintic agents may allow better penetration of worm body.…”
Section: Resultsmentioning
confidence: 99%
“…not necessarily causing cuticle damage). Pimentel-Acosta et al [14] also reported that silver nanoparticles at high and low concentrations activated dysregulation of similar biological processes (detoxi cation, neurotoxicity, modulation of cell signalling, embryonic development, reproduction, and tegument organization) by different mechanisms in metazoan parasites of sh. Since cuticle can act as a diffusion barrier for various anthelmintic compounds [15], combination of silver with conventional anthelmintic agents may allow better penetration of worm body.…”
Section: Resultsmentioning
confidence: 99%
“…not necessarily causing cuticle damage). Pimentel-Acosta et al [ 16 ] also reported that silver nanoparticles at high and low concentrations activated dysregulation of similar biological processes (detoxification, neurotoxicity, modulation of cell signaling, embryonic development, reproduction, and tegument organization) by different mechanisms in metazoan parasites of fish. Since cuticle can act as a diffusion barrier for various anthelmintic compounds [ 17 ], combination of silver with conventional anthelmintic agents may allow better penetration of worm body.…”
Section: Resultsmentioning
confidence: 99%
“…This toxicity can be modulated by changing the shape and size of the particles and modifying their surface, thanks to which we can obtain nanoparticles with the desired properties, and controlled toxicity [27,32]. An increasing number of studies confirm this potential [27,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. Currently, a significant number of nanosystems developed for medical use are composed of metallic nanoparticles with drug molecules attached to their surface, along with lipid particles or additional polymers.…”
Section: Introductionmentioning
confidence: 99%